b - Khieu, Samphan, author 1931- (Phnom Penh : Ponleu Khmer Print. & Pub. House, 2007)
Provides a chronological record of events happening in the Khmer Rouge Regime
Includes bibliographical references (p. [325])
Keywords: Parti communiste du Kampuchea; Cambodia -- Chronology -- History -- 1975-1979